2018
DOI: 10.1159/000491576
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Progesterone in Feto-Maternal Immunological Cross Talk

Abstract: This review aims to provide a brief historical overview of the feto-maternal immunological relationship, which profoundly influences the outcome of pregnancy. The initial question posed in the 1950s by Medawar [Symp Soc Exp Biol. 1953; 7: 320–338] was based on the assumption that the maternal immune system recognizes the fetus as an allograft. Indeed, based on the association between HLA-matching and spontaneous miscarriage, it became obvious that immunological recognition of pregnancy is required for a succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 86 publications
0
39
0
Order By: Relevance
“…As early as in the peri-implantation period, the embryo communicates with the endometrium releasing factors able to modulate these decidual immune cells [22,23]. Among these, soluble HLA-G, found in the embryonic secretome [24,25] is believed to represent a major player in the initiation of immunotolerance for the invading blastocyst into the decidual tissues.…”
Section: Preimplantation Embryo-derived Evs: Characterization and Rolmentioning
confidence: 99%
See 2 more Smart Citations
“…As early as in the peri-implantation period, the embryo communicates with the endometrium releasing factors able to modulate these decidual immune cells [22,23]. Among these, soluble HLA-G, found in the embryonic secretome [24,25] is believed to represent a major player in the initiation of immunotolerance for the invading blastocyst into the decidual tissues.…”
Section: Preimplantation Embryo-derived Evs: Characterization and Rolmentioning
confidence: 99%
“…Embryo-derived EVs have been also detected at the embryo-maternal interface in mouse implantation sites [23]. Pallinger and collaborators demonstrated that these EVs can transport progesterone-induced blocking factor (PIBF) [39].…”
Section: Evs and Progesterone-induced Blocking Factormentioning
confidence: 99%
See 1 more Smart Citation
“…T reg cells not only suppress fetal rejection, 9 but also account for the amelioration of autoimmune diseases observed during pregnancy, such as rheumatoid arthritis, 10,11 autoimmune hepatitis, 12 and multiple sclerosis. [14][15][16][17][18][19] However, recent findings suggest that the conventional nuclear progesterone receptor (PR) might not be expressed or might be expressed at a very low level in T cells. [14][15][16][17][18][19] However, recent findings suggest that the conventional nuclear progesterone receptor (PR) might not be expressed or might be expressed at a very low level in T cells.…”
Section: T Reg Cells Can Inhibit Effector T (T Eff )mentioning
confidence: 99%
“…13 A direct action of progesterone on T cells has long been postulated. [14][15][16][17][18][19] However, recent findings suggest that the conventional nuclear progesterone receptor (PR) might not be expressed or might be expressed at a very low level in T cells. 3,13 These contradictory observations on PR expression need further clarification.…”
Section: T Reg Cells Can Inhibit Effector T (T Eff )mentioning
confidence: 99%